Recovery and creative practices in people with severe mental illness: evaluating well-being and social inclusion - Saavedra, J.; Perez, Elvira; Crawford, Paul; Arias, S. (Taylor & Francis, 2018)
Purpose: This mixed (quantitative-qualitative) study evaluates the impact of an artistic workshop on a group of people with severe mental illness. This study focuses on the impact of creative practices on well-being and social inclusion outcomes. Method: After participating in a creative workshop, 31 people diagnosed with a severe mental illness completed pre/post-intervention measures, namely, the Warwick-Edinburgh Mental Well-Being Scale and the Social Inclusion questionnaire. It was applied in two-way repeated measures analysis of variance. The statistic Wilcoxon and Kruskal-Wallies were applied for non-parametric data to measure pre/post-test effects and workshop experience effects respectively. In addition to quantitative measures, one observer participated in each workshop that ran in parallel in order to deepen and triangulate quantitative outcomes. Results: The qualitative and quantitative results show that social inclusion improved in a significant way with an important size effect. Psychological wellbeing increased significantly with a low size effect. Conclusions: In accordance with these results, creative practices with people diagnosed with severe mental illness are recommended. In order to increase the impact of these interventions, it is recommended to utilize public space away from clinical environments and to include people without severe mental illness in creative activities together with severe mental illness patients.